2001
DOI: 10.1007/s002960000089
|View full text |Cite
|
Sign up to set email alerts
|

Pulmonary function tests, high-resolution computerized tomography, α1-antitrypsin measurement, and early detection of pulmonary involvement in patients with systemic sclerosis

Abstract: Restrictive lung disease was more pronounced in patients with dSSc. Alpha1-antitrypsin levels correlated significantly with ground glass opacities, an early finding of pulmonary involvement in SSc. Extent and severity of skin involvement and degree of dyspnea were not related to pulmonary involvement.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
17
0
1

Year Published

2005
2005
2016
2016

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(19 citation statements)
references
References 17 publications
1
17
0
1
Order By: Relevance
“…Other relevant causes of SSc include pulmonary ®brosis. In fact, no signi®cant correlation was observed between the degree of dyspnea and high-resolution computed tomography (HRCT) score, lung volumes, or DLco, as those same patients were already enrolled in another study where those investigations were performed and proved negative [20].…”
Section: Discussionmentioning
confidence: 91%
“…Other relevant causes of SSc include pulmonary ®brosis. In fact, no signi®cant correlation was observed between the degree of dyspnea and high-resolution computed tomography (HRCT) score, lung volumes, or DLco, as those same patients were already enrolled in another study where those investigations were performed and proved negative [20].…”
Section: Discussionmentioning
confidence: 91%
“…Semi-quantitative scores were not used to evaluate progression in this case [27]. Variations of this method also used by Pignone et al [2]; Davas et al [10]; Shahin et al [11]; Giacomelli et al [12]; Shah et al [13]; Gohari Moghadam [14]. …”
Section: Semi-quantitative Scoringmentioning
confidence: 99%
“…Studies using comparative scoring methods found correlation between higher HRCT severity grades and low DLCO, low FVC and low TLC [2,11,14]. When compared to biopsy specimen, mixed groundglass and reticular thickening (HRCT grade 3) corresponded to more inflammatory changes on histopathology.…”
Section: Validitymentioning
confidence: 99%
“…However, the advent of highresolution computed tomography (HRCT) has allowed a high sensitive examination of the entire lung parenchyma and pleura in many rheumatic diseases including AS [12][13][14][15]. Furthermore, it was demonstrated that HRCT of the thorax has a diagnostic superiority over plain radiography in the assessment of early pulmonary lesions [16,17].…”
Section: Introductionmentioning
confidence: 99%